Investigation of the Expression Levels of miR-155, miR-133a, and miR-146b in the Serum of Acute and Chronic Forms of Cutaneous Leishmaniasis - Hamedanipour, Mohammad; Khosravany, Zohre; Mirabedini, Zahra; Mohebali, Mehdi; Barati, Mohammad; Mirjalali, Hamed (Acta parasitologica, 2025)
Background Leishmaniasis is a vector-borne infectious disease caused by intracellular protozoan parasites of the genus Leishmania . MicroRNAs (miRNAs) can influence the progress and outcome of the disease. This study aimed to investigate the expression levels of miR-155, miR-133a, and miR-146b in the serum of acute and chronic forms of cutaneous leishmaniasis (CL) in Iran. Methods Samples were collected from 30 clinical cases of CL in Golestan province, who suffered from either acute or chronic forms of the disease, including 15 for each. Leishmania species were identified using PCR (kDNA gene). Total RNA was extracted from serum samples, complementary DNA (cDNA) was synthesized based on the loop technique, and the expression levels of miRNAs (miR-155, miR-133a, and miR-146b) were determined through quantitative real-time PCR analysis. Results Conventional PCR on kDNA confirmed the presence of L. major in 30 patients. Healing after one course of treatment and no response to treatment were considered as acute and chronic forms, respectively. Although there were no statistically significant changes, the expression of miR-133a and miR-155 was upregulated in patients with acute CL compared to those with chronic form, while miR-146b was downregulated in patients with acute CL. Conclusions In the current study, the expression changes of miR-155, miR-146b, and miR-133a in acute patients was compared to those patients with chronic CL. Although it was not significant, alterations in the expression levels of miRNAs were observed between acute and chronic forms of CL suggesting different pathogenesis of clinical forms.